2009
DOI: 10.1007/s00253-009-2098-1
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of steriodal saponins in Dioscorea zingiberensis C. H. Wright to diosgenin by Trichoderma harzianum

Abstract: Diosgenin is an important starting material in the steroidal hormone industry. Traditionally, diosgenin is mainly produced by acid hydrolysis of Dioscorea zingiberensis C. H. Wright (DZW) tubers. This method yields numerous byproducts that can cause serious pollution. In this study, diosgenin was obtained by biotransformation of steroidal saponins in DZW afforded by Trichoderma harzianum CGMCC 2979. The medium was optimized for maximum diosgenin production. The addition of phosphate buffer, surfactant Tween-85… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 17 publications
0
32
0
2
Order By: Relevance
“…6) Steroidal saponins are the major active components of DZW, and Deltonin, diosgenin-3-O-b -D-glucopyranosyl(1→4)-[a -L-rhamnopyranosyl(1→2)]-b-D-glucopyranoside, is one of the main constituents of these steroidal saponins. [7][8][9] In our previous study, we found that Deltonin was effective in the treatment of cancer cells and was able to induce cancer cell apoptosis both in vitro and in vivo. 10) In the present study, we investigated the anticancer effect of Deltonin on a panel of cancer cell lines and analyzed its mechanism in C26 cells.…”
mentioning
confidence: 99%
“…6) Steroidal saponins are the major active components of DZW, and Deltonin, diosgenin-3-O-b -D-glucopyranosyl(1→4)-[a -L-rhamnopyranosyl(1→2)]-b-D-glucopyranoside, is one of the main constituents of these steroidal saponins. [7][8][9] In our previous study, we found that Deltonin was effective in the treatment of cancer cells and was able to induce cancer cell apoptosis both in vitro and in vivo. 10) In the present study, we investigated the anticancer effect of Deltonin on a panel of cancer cell lines and analyzed its mechanism in C26 cells.…”
mentioning
confidence: 99%
“…The fermentation broth was obtained from the biotransformation of DZW dried root powder under optimized conditions, as described previously [8]. T. harzianum is preserved at the China General…”
Section: Methodsmentioning
confidence: 99%
“…Four hundred microlitres each of the middle and bottom phases were added to two volumes of anhydrous methanol, and the mixture was vigorously mixed by inversion and then centrifuged at 12,000 rpm for 15 min. The supernatant was collected and analysed by analytical HPLC [8]. The samples were analysed with a Waters 600E multi-solvent delivery system (Agilent, America) equipped with a Sunfire C18 column, 44% A→75% A; 14-15 min, 75% A→91% A; and 15-32 min, 91% A.…”
Section: Effects Of the Ammonium Sulphate And Ethanol Concentrations mentioning
confidence: 99%
See 1 more Smart Citation
“…However, to our knowledge, there were very few reports on screening of microorganism of highly efficient biotransformation of dioscin to diosgenin and no reports on direct biotransformation of RDZ, which was simple and more practical. Several literatures reported biotransformation of extracted steroidal saponins to diosgenin, but of low biotransformation rate [13][14][15]; furthermore, extraction of dioscin is relatively of high cost, which makes it less applicable in the biotransformation procedure. So related researches should be focused on screening of microorganism species with high activity and developing a highly efficient biotransformation system.…”
Section: Introductionmentioning
confidence: 99%